1993
DOI: 10.1152/jn.1993.69.6.1948
|View full text |Cite
|
Sign up to set email alerts
|

Exploring parameter space in detailed single neuron models: simulations of the mitral and granule cells of the olfactory bulb

Abstract: 1. Detailed compartmental computer simulations of single mitral and granule cells of the vertebrate olfactory bulb were constructed using previously published geometric data. Electrophysiological properties were determined by comparing model output to previously published experimental data, mainly current-clamp recordings. 2. The passive electrical properties of each model were explored by comparing model output with intracellular potential data from hyperpolarizing current injection experiments. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 43 publications
(21 reference statements)
5
147
0
4
Order By: Relevance
“…1A). This illustrates an important general principle, namely, that similar electrophysiological behavior can arise from widely disparate sets of underlying conductances (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Fig.…”
Section: Multiple Solutions and Failure Of Averagingmentioning
confidence: 78%
“…1A). This illustrates an important general principle, namely, that similar electrophysiological behavior can arise from widely disparate sets of underlying conductances (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Fig.…”
Section: Multiple Solutions and Failure Of Averagingmentioning
confidence: 78%
“…The statistical modeling approach that we have used accurately captures the neuronal properties determining spiking and avoids overfitting. It also avoids making specific but difficult-to-verify claims about channel densities or properties that can arise from underconstrained Hodgkin-Huxley models (36). We show that diverse populations offer the advantages of more efficient encoding (defined in terms of information per cell or information per spike) and more robust coding of different kinds of stimuli, such as stimuli with wide ranges of spectral properties.…”
Section: Discussionmentioning
confidence: 99%
“…A statistical proof called the Schema Theorem guarantees improvement of the search over time (Holland 1975). EAs have not previously been applied to the field of compartmental neuronal modeling, although reduced dimensional parameter searches using systematic (Bhalla and Bower 1993) or stochastic (Foster et al 1993) search methods have been reported. Would these or methods other than an EA perform better?…”
Section: Why Use Evolutionary Algorithms?mentioning
confidence: 99%